6-Thio-substituted-2H-(1,2,4)triazino(2,3-c)quinazolin-2-ones with the dialkylaminoethyl moiety – a new class of antivirial agents - Voskoboynik, O. Yu.; Berest, G. G.; Nosulenko, I. S.; Antypenko, L. M.; Krivoschey, O. V; Shvets, V. M.; Kovalenko, S. I.; Воскобойнік, Олексій Юрійович; Берест, Галина Григорівна; Носуленко, Інна Степанівна; Антипенко, Людмила Миколаївна; Кривошей, Оксана Вікторівна; et al. (My University, 2016)
It has been found that 6-[(β-dialkylaminoethylthio]-3-R-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones exhibit the antiviral activity against respiratory and the biodefence virus panel (ЕС50 3.2-36.0 mg/ml) and the influenza type A and B (ЕС50 1.1-18.0 mg/ml) in the visual (viral CPE) and neutral red dye uptake increasing tests. The high inhibitory activity of compound 1.5 against the strain Flu B (ЕС50 1.1-5.3 mg/ml) has been revealed. It has been suggested that the antiviral effect of compound 1.5 is comparable with Ribavirin. It has been shown that the planar [1,2,4]triazino[2,3-c]quinazoline system causes antiviral properties additionally determined by the b-dialkylaminoethylthiol fragment and depends on the nature of the substituent in position 3.Встановлено, що 6-[(β-діалкіламіноалкілтіо]-3-R-2H-[1,2,4]триазино[2,3-c]хіназолін-2-oни проявляють противірусну активність у візуальному тесті (viral CPE) і тесті підвищення захвату барвника нейтрального червоного (neutral red) щодо респіраторних і особливо небезпечних вірусів (ЕС50 3.2-36.0 mg/ml) та вірусу грипу A&B (ЕС50 1.1-18.0 mg/ml). Виявлена висока інгібуюча концентрація у сполуки 1.5 щодо штаму вірусу грипу B (ЕС50 1.1-5.3 mg/ml), яка конкурує з препаратом порівняння Рибаверином (ЕС50 0.19-1.0 mg/ml). Показано, що планарна [1,2,4]триазино[2,3-c]хіназолінова система є носієм противірусної активності, яка додатково визначається ліпофільним b-діалкіламіноетилтіольним фрагментом і залежить від будови арильного замісника у третьому положенні.
6-Тioзаміщені 2H-[1,2,4]триазино[2,3-c]хіназолін-2-oни з діалкіламіноетильним фрагментом – новий клас противірусних агентів
6-Тиозамещенные 2H-[1,2,4]триазино[2,3-c]хиназолин-2-oны с диалкиламиноэтильным фрагментом – новый класс противовирусных агентов
Keywords: biodefence viruses; respiratory viruses; antiviral activity; особенно опасные вирусы; респираторные вирусы; противовирусная активность; особливо небезпечні віруси; респіраторні віруси; противірусна активність